Association of Headache Disorders and the Risk of Dementia: Meta-Analysis of Cohort Studies - Qu, Huiling; Yang, Shida; Yao, Zhicheng; Sun, Xiaoyu; Chen, Huisheng (Frontiers in Aging Neuroscience, 2022)
Objectives: The purpose of this meta-analysis is to assess whether there is an association between headache disorders and all-cause dementia, Alzheimer’s disease (AD), and vascular dementia (VaD). Methods: PubMed, Cochrane Library, Embase, and Web of Science were searched for cohort studies published from database inception to October 8, 2021, using medical subject headings (MeSH) and keywords. All statistical analyses were performed using Stata statistical software version 14.0. If P > 0.1 and I2 ≤ 50%, a fixed-effects model was adopted. If I2 > 50% (which indicated great heterogeneity), a random-effects model was adopted. The funnel plot and Egger’s test were used to evaluate publication bias. Results: This meta-analysis included 12 cohort studies covering 465,358 individuals, which were published between 2001 and 2020. The pooling analysis shows that a history of any headache disorder is associated with an increased risk of all-cause dementia (OR = 1.35; 95% CI: 1.21–1.50; I2 = 81.6%, P < 0.001). The history of any headache was associated with an increased risk of AD (OR = 1.49; 95% CI: 1.08–2.05; I2 = 70.0%, P = 0.003) and VaD (OR = 1.72; 95% CI: 1.32–2.25; I2 = 0%, P < 0.001). In the subgroup analysis, females with a history of headache have a slightly higher risk of dementia than males (OR = 1.32; 95% CI: 1.16–1.51; I2 = 88.3%, P < 0.001) and the risk of dementia in the retrospective cohort was slightly higher than in the prospective cohort (OR = 1.38; 95% CI: 1.22–1.56; I2 = 83.4%, P < 0.001). Conclusions: Our meta-analysis shows that any headache disorder increases the risk of all-cause dementia, AD, or VaD. These findings provide evidence that headache should be recognized as an independent risk factor for dementia, AD, or VaD.